2023
DOI: 10.1208/s12249-023-02518-7
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach for Formulation of Rutin Tablets Targeted for Colon Cancer Treatment

Abstract: The aim of this study was the improvement of rutin solubility along with targeting its release to colon for effective treatment of colon cancer. Five formulations of compression-coated tablets were prepared with the same core composition including rutin-polyvinyl pyrrolidone K30 solid dispersion (rutin-PVP K30 SD) but differ in being coated with either frankincense alone or different combinations of frankincense with gelatin. The superior formula was selected based on the in vitro drug release then further eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…However, MIT and DOX caused significant shrinkage of PCa and BCa tumors, respectively, suggesting the anticancer capacity of such typical chemotherapeutic agents is generally higher than that of rapamycin and rutin (senomorphics) when used alone, especially in the experimental settings of our study. Although former studies reported the effectiveness of these agents in cancer treatments (Ismail et al, 2023 ; Yin et al, 2023 ), the virtual efficacy of each of these senomorphics may be dependent on a number of specified factors such as the pharmacological dose, cancer type, and administration schedule of anticancer regimens.…”
Section: Discussionmentioning
confidence: 99%
“…However, MIT and DOX caused significant shrinkage of PCa and BCa tumors, respectively, suggesting the anticancer capacity of such typical chemotherapeutic agents is generally higher than that of rapamycin and rutin (senomorphics) when used alone, especially in the experimental settings of our study. Although former studies reported the effectiveness of these agents in cancer treatments (Ismail et al, 2023 ; Yin et al, 2023 ), the virtual efficacy of each of these senomorphics may be dependent on a number of specified factors such as the pharmacological dose, cancer type, and administration schedule of anticancer regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Nafees et al [36] showed that rutin in combination with silibinin produces synergistic anti-cancer effects on HT29 CRC cells by regulating expression of apoptosis, inflammation, and MAPK pathway proteins. Recently, a new colonic delivery method for rutin was studied by formulating rutin into frankincense-based compression-coated tablets and showed that the anti-cancer effect was improved [37]. Interestingly, network pharmacology and analysis of gene biological information showed that the potential intracellular signaling pathways of rutin in human SW480 cells may be associated with miRNAs-long noncoding RNAs (lncRNAs)-messenger RNAs-transcription factors [38].…”
Section: Rutinmentioning
confidence: 99%
“…Nanocrystal-loaded tablets dissolved completely within 30 min, while market tablets dissolved about 60% of rutin. , The solid dispersions of rutin were obtained by solvent evaporation at a weight ratio of 1:1. Rutin-PVP K30 SD exhibited a higher equilibrium solubility compared with pure rutin . Paczkowska et al obtained a rutin-β-cyclodextrin complex by cogrinding, and the solubility of rutin and the rutin-β-cyclodextrin complex was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Rutin-PVP K30 SD exhibited a higher equilibrium solubility compared with pure rutin. 32 Paczkowska et al obtained a rutin-β-cyclodextrin complex by cogrinding, and the solubility of rutin and the rutin-β-cyclodextrin complex was studied. The rutin-β-cyclodextrin complex showed higher solubility in different buffers.…”
Section: ■ Introductionmentioning
confidence: 99%